2022
DOI: 10.3390/ijms23126829
|View full text |Cite
|
Sign up to set email alerts
|

Optineurin Deficiency and Insufficiency Lead to Higher Microglial TDP-43 Protein Levels

Abstract: Mutations in optineurin, a ubiquitin-binding adaptor protein, cause amyotrophic lateral sclerosis (ALS), a fatal neurodegenerative disease of motor neurons linked to chronic inflammation and protein aggregation [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Lastly, we checked for the presence of TDP-43 protein aggregation. Because of the reportedly different preferential staining of cytoplasmic aggregates and nuclear TDP-43 by antibodies targeting the C- and N-terminus of TDP-43 26 , we used both antibodies. None of the anti-TDP-43 antibodies detected cytoplasmic aggregates (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we checked for the presence of TDP-43 protein aggregation. Because of the reportedly different preferential staining of cytoplasmic aggregates and nuclear TDP-43 by antibodies targeting the C- and N-terminus of TDP-43 26 , we used both antibodies. None of the anti-TDP-43 antibodies detected cytoplasmic aggregates (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, models carrying optineurin C-terminal truncation (Optn 470T ) or point mutation (Optn D477N ), mimicking some ALS patient mutations that disrupt ubiquitin binding, showed no overt neuroinflammation or ALS pathology (at two months, and one year, respectively) 18 , 24 . Isolated primary microglia from the Optn 470T mouse model showed decreased activation of TBK1 and subsequent interferon (IFN)-β production 24 , but no defect in microglial phagocytosis 25 or TDP-43 aggregation 26 . However, detailed characterisation and/or long-term repercussions of the ubiquitin-binding optineurin mutations in the in vivo models are lacking so it is unknown if these models are similar or distinct to Optn −/− mice.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we checked for the presence of TDP-43 protein aggregation. Because of the reportedly different preferential staining of cytoplasmic and nuclear TDP-43 by antibodies targeting the C- and N-terminus of TDP-43, respectively (26), we used both antibodies. None of the anti-TDP-43 antibodies detected cytoplasmic aggregates (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, models carrying optineurin C-terminal truncation (Optn 470T ) or point mutation (Optn D477N ), mimicking some ALS patient mutations that disrupt ubiquitin-binding, showed no overt neuroinflammation or ALS pathology (at two months, and one year, respectively) (17,24). Isolated primary microglia from the Optn 470T mouse model showed decreased activation of TBK1 and subsequent interferon (IFN)-β production (24), but no defect in phagocytosis (25) or TDP-43 aggregation (26). However, detailed characterisation and/or long-term repercussions of the ubiquitin-binding optineurin mutations in the in vivo models are lacking so it is unknown if these models are similar or distinct to Optn -/- mice.…”
Section: Introductionmentioning
confidence: 99%
“…ALS can be caused by OPTN gene mutations, which result in cytoplasmic mislocalization, ubiquitination, and accumulation of nuclear TDP-43. Prtenjaca et al (2022) used CRISPR/Cas9 methodology to create OPTN knockout (KO) cell lines for Neuro 2a and NSC-34 neurons and BV2 microglia to investigate the relationship between optineurin and TDP-43. Their research showed that OPTN mutations might lead to elevated levels of TDP-43 protein in microglia when optineurin is absent (Prtenjaca et al, 2022).…”
Section: Amyotrophic Lateral Sclerosis Model Constructionmentioning
confidence: 99%